Comparison of Socal Score and Hasford Score Against the Response of Imatinib Mesylate Therapy in Patients with Chronic Granulocytic Leukemia in dr. Saiful Anwar Hospital Malang - Somarnam, Somarnam; Machsoos, Budi Darmawan; Hermanto, Djoko Heri (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. The Socal and Hasford scores developed before the era of tirosine kinase inhibitor (TKI) therapy to provide predictions and prognosis for the results of therapy for chronic myeloid leukemia patients (CML). Until now the superiority of Socal and Hasford scores is still debated in predicting the results of therapy in the era of TKI. Imatinib mesylat is a first line TKI in the treatment of CML. This study aims to determine the superior predictive score in predicting hematological and molecular response of patients treated with imatinib mesylate. Methods. A survey study was conducted with data taken retrospectively from medical records. Subjects were chronic phase LGK patients who had at least been given imatinib mesylate therapy for 12 months. Calculation of Socal and Hasford scores was carried out based on patient data when first receiving Imatinib. To see the difference in distribution between the two scores, a marginal homogeneity statistic was used. To see the process of changing the response of patients treated with Imatinib, a suitability test using chi-square and Fischer was conducted with a significant p value, p 0,05. Conclusion. There was no significant difference between Hasford and Socal scores in predicting hematological responses and molecular responses of chronic CML patients. Socal scores and Hasford scores can be used to predict hematological and molecular responses in chronic CML patients treated with imatinib mesylate.